Phylogeny and PCR Identification of Clinically Important Zygomycetes Based on Nuclear Ribosomal-DNA Sequence Data - Voigt, Kerstin (American Society for Microbiology, 1999)
A molecular database for all clinically important Zygomycetes was constructed from nucleotide sequences from the nuclear small-subunit (18S) ribosomal DNA and domains D1 and D2 of the nuclear large-subunit (28S) ribosomal DNA. Parsimony analysis of the aligned 18S and 28S DNA sequences was used to investigate phylogenetic relationships among 42 isolates representing species of Zygomycetes reported to cause infections in humans and other animals, together with commonly cultured contaminants, with emphasis on members of the Mucorales. The molecular phylogeny provided strong support for the monophyly of the Mucorales, exclusive of Echinosporangium transversale and Mortierella spp., which are currently misclassified within the Mucorales. Micromucor ramannianus, traditionally classified within Mortierella, and Syncephalastrum racemosum represent the basal divergences within the Mucorales. Based on the 18S gene tree topology, Absidia corymbifera and Rhizomucor variabilis appear to be misplaced taxonomically. A. corymbifera is strongly supported as a sister group of the Rhizomucor miehei-Rhizomucor pusillus clade, while R. variabilis is nested within Mucor. The aligned 28S sequences were used to design 13 taxon-specific PCR primer pairs for those taxa most commonly implicated in infections. All of the primers specifically amplified DNA of the size predicted based on the DNA sequence data from the target taxa; however, they did not cross-react with phylogenetically related species. These primers have the potential to be used in a PCR assay for the rapid and accurate identification of the etiological agents of mucormycoses and entomophthoromycoses.